Successful Treatment of Relapsed/Refractory Extramedullary Multiple Myeloma With Anti-BCMA CAR-T Cell Therapy Followed by Haploidentical Hematopoietic Stem Cell Transplantation: A Case Report and a Review of the Contemporary Literature - Qian, Ying; Qian, Zijun; Zhao, Xiujie; Pan, Wenjue; Wei, Xinzheng; Meng, Huimin; Yang, Lin; Xiao, Haowen (Frontiers in Medicine, 2021)
Extramedullary multiple myeloma (EMM) is an aggressive sub-entity of multiple myeloma (MM). Despite an excellent improvement in survival for most patients with MM over recent decades, the overall survival (OS) of patients with EMM was usually not longer than 3 years. Standard treatment for patients with EMM has not been established and their management is particularly challenging. We explored the use of a chimeric antigen receptor (CAR) T-cell therapy that targeted B-cell maturation antigen (BCMA) (NCT04650724), followed by salvage haploidentical hematopoietic stem cell transplantation (HSCT), for a heavily pretreated patient with relapsed EMM and refractoriness to a proteasome inhibitor (PI; bortezomib), a next-generation PI (ixazomib) , immunomodulatory drugs (IMiDs; lenalidomide), autologous hematopoietic stem cell transplantation (ASCT) and monoclonal antibody (directed against CD38: daratumumab). Taken together of the contemporary literature, the promising results on the effect of anti-BCMA CAR-T cell therapy and allogeneic HSCT might present a proof-of-principle for patients with EMM and therefore patients with the disease need to be included in future studies.